Characterization of Locally Excited and Charge‐Transfer States of the Anticancer Drug Lapatinib by Ultrafast Spectroscopy and Computational Studies. Issue 68 (22nd October 2020) - Vayá, Ignacio; Andreu, Inmaculada; Lence, Emilio; González‐Bello, Concepción; Consuelo Cuquerella, M.; Navarrete‐Miguel, Miriam; Roca‐Sanjuán, Daniel; Miranda, Miguel A.
Abstract: Lapatinib (LAP) is an anticancer drug, which is metabolized to the N ‐ and O‐dealkylated products ( N ‐LAP and O ‐LAP, respectively). In view of the photosensitizing potential of related drugs, a complete experimental and theoretical study has been performed on LAP, N ‐LAP and O ‐LAP, both in solution and upon complexation with human serum albumin (HSA). In organic solvents, coplanar locally excited (LE) emissive states are generated; they rapidly evolve towards twisted intramolecular charge‐transfer (ICT) states. By contrast, within HSA only LE states are detected. Accordingly, femtosecond transient absorption reveals a very fast switching (ca. 2 ps) from LE ( λ max =550 nm) to ICT states ( λ max =480 nm) in solution, whereas within HSA the LE species become stabilized and live much longer (up to the ns scale). Interestingly, molecular dynamics simulation studies confirm that the coplanar orientation is preferred for LAP (or to a lesser extent N ‐LAP) within HSA, explaining the experimental results. Abstract : Ultra–faster than fast : The photophysical properties of the anticancer drug lapatinib and two of its metabolites have been fully characterized in solution and in the presence of human serum albumin by means of ultrafast spectroscopy and computational studies. All results indicate that the geometrical arrangement controls their photobehavior. Thus, in a coplanar orientation locally excited states are formed whereas in a twisted positioning intramolecular charge‐transfer states prevail.